Current land-based farming systems research and future challenges - Editors (New Zealand Science Review, 2019)
The Ministry of Business, Innovation and Employment (MBIE) has released a report by Sapere Research Group identifying global trends likely to affect the future of food and farming, and the implications for New Zealand’s science and innovation system.The report identified three international trends: 1. Enhanced environmental consciousness: Global consumers are increasingly demanding products that fulfil a growing range of environmental demands. 2. New technological developments and transformational science: These developments include advances in the science of genomics, plant-based proteins and cellular agriculture. 3. Changing consumer preferences and other trends: In addition to environmental and animal welfare concerns, consumers will continue to raise demand for quality, food safety, health benefits, provenance,ethics, and biosecurity. MBIE commissioned this report to better understand the role of science and innovation in responding to potentially disruptive and transformative changes in agriculture and food production.